Polyphosphate affects the growth and methanogenesis of deep-sea methanogenic archaea - Rikuan Zheng; Chong Wang; Yuxin Zheng; Lei Cao; Kaitao Liu; Jie Li; Chaomin Sun (Proceedings of the National Academy of Sciences, 2026)
Microorganisms employ inorganic polyphosphate (polyP) as an ancient strategy for energy and phosphate storage, yet its physiological roles in methanogenic archaea remain largely unexplored. Here, we report that polyP metabolism is coupled to growth and methanogenesis in Methanolobus sp. ZRKC1, a representative of eight methanogenic archaea isolated from deep-sea cold seep sediments. Through combined genetic, biochemical, and physiological analyses, we find that PPK1 mediates polyP synthesis in a Mg 2+ -dependent manner, whereas PPK2 functions primarily as a polyP hydrolase. Deletion of ppk1 in strain ZRKC1 abolishes polyP accumulation and impairs both growth and methane production, pointing to a role for polyP as a metabolic hub linking these processes. Transcriptomic profiling reveals that under organic phosphorus conditions, strain ZRKC1 upregulates phosphoesterases to liberate bioavailable phosphate, which is subsequently channeled into polyP via PPK1. Furthermore, in situ transcriptomic data suggest that the genetic capacity for this metabolic strategy may be present and transcriptionally active in the native environment, with concurrent upregulation of genes involved in phosphate acquisition, polyP metabolism, and methanogenesis. Our findings suggest the importance of polyP in linking phosphate homeostasis to growth and methanogenesis in deep-sea methanogenic archaea.